2010
DOI: 10.1016/j.medin.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiología de las bacteriemias primarias y relacionadas con catéteres vasculares en pacientes críticos ingresados en servicios de medicina intensiva

Abstract: The empirical treatment in situations of extreme seriousness should consider coverage of the most frequent pathogens such as the MR-GPC and GNB and in special conditions, the fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Compared to other studies, there also is a difference in the type of Gram-negative micro-organism found on the catheter tips. Previous studies found E. coli , Klebsiella species, and, in ICUs, Enterobacter species as the most important micro-organisms on intravascular catheter tips [1, 3, 4]. We found E. cloacae on most of the catheter tips, followed by P. aeruginosa and K. pneumoniae .…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…Compared to other studies, there also is a difference in the type of Gram-negative micro-organism found on the catheter tips. Previous studies found E. coli , Klebsiella species, and, in ICUs, Enterobacter species as the most important micro-organisms on intravascular catheter tips [1, 3, 4]. We found E. cloacae on most of the catheter tips, followed by P. aeruginosa and K. pneumoniae .…”
Section: Discussionsupporting
confidence: 47%
“…Intravascular catheters are a significant source of bloodstream infections in hospitalized patients [13]. In Europe, the overall incidence of nosocomial bloodstream infections is five episodes per 1,000 days of in situ central venous catheter (CVC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations